2003
DOI: 10.1159/000075926
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Pantoprazole Compared with Misoprostol for the Prevention of NSAID-Related Gastrointestinal Lesions and Symptoms in Rheumatic Patients

Abstract: Aim: To compare the efficacy and tolerability of pantoprazole 20 mg once daily (o.d.) with misoprostol 200 µg twice daily (b.i.d.), administered for 6 months to rheumatic patients who required long-term therapy with nonsteroidal anti-inflammatory drugs (NSAIDs) and who were at increased risk of developing gastrointestinal lesions. Methods: This randomized, double-blind, multicenter, parallel group comparison study was performed with rheumatic patients (n = 515) who were likely to take NSAIDs continuously for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
1
21
0
2
Order By: Relevance
“…Our data on pantoprazole are consistent with other studies indicating that PPIs are efficacious in reducing NSAID-induced mucosal lesions and complications [2,15]. Two identical trials on the efficacy of esomeprazole 20 and 40 mg once daily for the relief of upper GI symptoms in patients using NSAIDs were recently published showing a consistent trend for higher efficacy with the lower dose [16].…”
Section: Discussionsupporting
confidence: 90%
“…Our data on pantoprazole are consistent with other studies indicating that PPIs are efficacious in reducing NSAID-induced mucosal lesions and complications [2,15]. Two identical trials on the efficacy of esomeprazole 20 and 40 mg once daily for the relief of upper GI symptoms in patients using NSAIDs were recently published showing a consistent trend for higher efficacy with the lower dose [16].…”
Section: Discussionsupporting
confidence: 90%
“…3 Control of gastric acidity using acid-suppressive therapy has been proposed as an effective means of healing ulcers [6][7][8][9][10][11] and controlling and preventing NSAID-associated upper GI injury and ulcer complications. 8,9,[12][13][14][15][16] Although both H 2 RAs and PPIs can be used as acid-suppressive agents in the treatment of other disease states, PPIs are preferable to standard doses of H 2 RAs for preventing NSAID-associated endoscopic injury. 9,20 Results of recent studies have shown that esomeprazole treatment significantly decreased the development of ulcers associated with the use of COX-2-selective and non-selective NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…5 The clinical correlate of the pivotal role of gastric acid in the development of gastroduodenal mucosal injury is that proton pump inhibitor (PPI) co-therapy has been shown to heal, maintain healing and reduce the risk of developing NSAIDrelated ulcers [6][7][8][9][10][11] and to decrease NSAID-related upper gastrointestinal (GI) symptoms. 8,9,12,13 Practice guidelines often recommend co-prescribing an acid inhibitor, such as a PPI, with NSAIDs in patients at risk of developing GI complications. [14][15][16] However, no studies have compared the pharmacodynamic actions of different PPIs in controlling intragastric acidity in patients using NSAIDs.…”
Section: Introductionmentioning
confidence: 99%
“…Pantoprazole has a higher chemical stability at neutral and moderately acidic pH compared with other PPIs, which makes it less likely to become activated in moderately acidic compartments of the body. Most importantly, it has a low potential for metabolic interactions with cytochrome P450-dependent oxidase system and so it is particularly suitable for patients in co-medications (Stupnicki et al 2004). …”
Section: Efficacy Safety and Tolerability Of Pantoprazolementioning
confidence: 99%